A mixed‐methods evaluation of a health‐promoting café located in a small health service in rural Victoria, Australia. (27th July 2022) - Whelan, Jillian; Love, Penelope; Aitken, John; Millar, Lynne; Morley, Catherine; Melgren, Ngareta; Allender, Steven; Bell, Colin
Abstract: Introduction: Residents of rural areas internationally typically experience chronic disease risk profiles worse than city dwellers. Poor diet, a key driver of chronic disease, has been associated with unhealthy food environments, and rural areas often experience limited access to healthy, fresh and affordable food. Objective: This study aimed to evaluate the first three years of a health promoting social enterprise café established in a small rural health service. Design: A mixed‐methods evaluation study. Quantitative sales data, surveys and key informant interviews that included both quantitative and qualitative responses. Findings: Three years of sales data were included; 111customer surveys and five key informant interviews were conducted. Food and beverages on displayed and sold consistently met or exceeded the healthy criteria set by policy. Stakeholders supported the traffic light system, the social enterprise model and rated the likelihood of sustainability of the café as high. Discussion: Customers used the 'traffic light' system to inform food choices, placed value on the warmth of the staff and on the welcoming environment created through the social enterprise model. Resources remain tight although all stakeholders are committed to the sustainability of the YarriYak café. Conclusion: The study shows the acceptability, feasibility and sustainability of a health promoting social enterprise café in a rural area.